Cerebral Amyloid Angiopathy Related Inflammation With Prominent Meningeal Involvement. A Report of 2 Cases - Aghetti, Agnès; Sène, Damien; Polivka, Marc; Shor, Natalia; Lechtman, Sarah; Chabriat, Hugues; Jouvent, Eric; Guey, Stéphanie (Frontiers in Neurology, 2019)
Cerebral amyloid angiopathy related inflammation (CAA-RI) is a rare form of CAA characterized by subacute encephalitic symptoms (cognitive decline, seizures, focal deficits) associated with extensive and confluent white matter lesions co-localizing with lobar microbleeds on brain MRI. We report two cases of unusual CAA-RI mimicking meningoencephalitis but without typical brain lesions on FLAIR and T2* sequences. These 2 cases may extend the clinical spectrum of CAA-RI by suggesting the possible occurrence of quite purely meningeal forms of CAA-RI.